Automotive Window Glass
Patent Information
- Application Number
- JP2019139271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-07-29
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2039-07-29
AI Technical Summary
【0014】 本発明に係る自動車用窓ガラスによれば、ガラス板上に機能膜を直接積層することができる。
Smart Images

Figure 0007638059000008 
Figure 0007638059000009 
Figure 0007638059000010
Abstract
Description
[Technical field]
[0001] The present invention relates to automotive glazings. [Background technology]
[0002] Automobile window glass is laminated with various functional films that exhibit water-repellent properties, light-shielding properties, etc. Such functional films are laminated by various methods, and for example, Patent Document 1 discloses an automobile window glass in which a base layer is formed on a glass plate, and a water-repellent film is laminated thereon as a functional film. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-285574 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, forming a water-repellent film after forming an undercoat layer increases the number of steps, which is a problem. The present invention has been made to solve the above problem, and has an object to provide an automobile window glass that allows a functional film to be directly laminated on a glass sheet without using an undercoat layer. [Means for solving the problem]
[0005] Item 1. Automotive window glass, A glass plate and a first functional film having a water-repellent function laminated on the glass plate; Equipped with the first functional film contains a coupling agent having an alkoxysilyl group; For the first functional film, dry cloth is applied at 1200g / 4cm 2 After being reciprocated 1,500 times under a load of 100°, the contact angle of water on the first functional film is 100° or more.
[0006] Item 2. The automobile window glass according to item 1, wherein the first functional film has a thickness of 5 to 50 nm.
[0007] Item 3. The automobile window glass according to item 1 or 2, wherein a water sliding angle in the first functional film is 20° or less.
[0008] Item 4. The automobile window glass according to any one of Items 1 to 3, wherein the first functional film has a surface roughness Ra of 0.5 to 3.0 nm.
[0009] Item 5. The automotive window glass according to any one of Items 1 to 4, which is a side glass that can be raised and lowered.
[0010] Item 6. The automobile window glass according to any one of Items 1 to 5, wherein the first functional film is formed so that a film thickness varies in a surface direction.
[0011] Item 7. The automobile window glass according to item 6, wherein the first functional film is formed so that projections and recesses are arranged in one of the surface directions, and the pitch between adjacent projections is 20 to 150 mm.
[0012] Item 8. The first functional film is laminated on one surface of the glass plate, A second functional film is laminated on the other surface of the glass plate, Item 8. The automobile window glass according to any one of items 1 to 7, wherein the second functional film contains the same composition as the composition that exerts the water repellent function of the first functional film.
[0013] Item 9. The automobile window glass according to item 8, wherein the first functional film and the second functional film have the same content of the composition exhibiting the water-repellent function. Effect of the Invention
[0014] According to the automotive window glass of the present invention, a functional film can be directly laminated on the glass sheet. [Brief description of the drawings]
[0015] [Figure 1] 1 is a plan view showing an embodiment in which an automobile window glass according to the present invention is applied to a side window. [Diagram 2] 2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] 4 is a schematic diagram illustrating the bonding between a first functional film and a glass plate. FIG. [Figure 4] FIG. 4 is a cross-sectional view illustrating the measurement of the thickness of the first functional film. [Diagram 5] FIG. 2 is a diagram illustrating application of a coating liquid for a first functional film by spraying. [Figure 6] 4 is a cross-sectional view illustrating unevenness occurring in a first functional film. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] First, an embodiment in which an automobile window glass according to the present embodiment is applied to a side glass will be described with reference to the drawings using Figures 1 and 2. Figure 1 is a plan view of the side glass according to the present embodiment, and Figure 2 is a cross-sectional view taken along line AA in Figure 1.
[0017] <1. Overview of side glass> 1 and 2, this side glass includes a trapezoidal glass plate 1 and a first functional film 2 laminated on an interior surface 101 of this glass plate 1. A detailed description will be given below.
[0018] <1-1. Glass plate> Each glass plate 1 is formed in a rectangular shape having an upper side 11, a lower side 12, a front side 13, and a rear side 14. The upper side 11 and the lower side 12 are formed in parallel, and the upper side 11 is shorter than the lower side 12. The front side 13 has a first portion 131 that extends upward from the front end of the lower side 12 so as to be inclined toward the rear, and a second portion 132 that extends from the upper end of the first portion 131 so as to be inclined further toward the rear. The rear side 14 extends upward from the rear end of the lower side 12 so as to be inclined toward the rear while being slightly curved toward the rear, approximately parallel to the first portion 131 of the front side 13. Therefore, the rear end of the upper side 11 is located slightly behind the rear end of the lower side 12.
[0019] The side glass composed of the outer glass plate 1 and the inner glass plate 2 is attached to the door of the vehicle, and is supported by a lifting module (regulator) (not shown) provided inside the door, and is adapted to be lifted and lowered. When the side glass is lifted and the window is closed, the lower edge 12 of the side glass is located below the belt molding of the door. Therefore, the lower edge 12 of the side glass is not visible from the outside and inside of the vehicle, regardless of whether the window is open or closed. In addition, during the process of lifting the side glass, the first portion 131 and the rear edge 14 of the front side edge 13 are supported by a guide (e.g., a glass run) of the door frame, and move up and down along this guide. Therefore, the first portion 131 and the rear side edge 14 of the front side edge 13 are accommodated in the guide, and are not visible from the outside and inside of the vehicle. When the window is closed, the second portion 132 and the upper edge 11 of the front side edge 13 are also accommodated in the door frame, and are not visible from the outside and inside of the vehicle.
[0020] A known glass plate can be used as the glass plate 1, and it can be made of heat absorbing glass, general clear glass, green glass, or UV green glass. Examples of compositions of clear glass, heat absorbing glass, and soda lime glass are shown below.
[0021] (Clear glass) SiO 2 :70~73% by mass Al 2 O 3 :0.6~2.4% by mass CaO: 7~12% by mass MgO: 1.0~4.5% by mass R 2 O: 13 to 15 mass% (R is an alkali metal) Fe 2 O 3 Total iron oxide (T-Fe 2 O 3 ):0.08~0.14% by mass
[0022] (Heat absorbing glass) The composition of heat absorbing glass is, for example, based on the composition of clear glass, Fe 2 O 3 Total iron oxide (T-Fe 2 O 3 ) is 0.4 to 1.3 mass%, and CeO 2 The ratio of TiO is 0 to 2 mass%. 2 The ratio of is 0 to 0.5 mass%, and the glass framework component (mainly SiO 2 Or Al 2 O 3 ) to T-Fe 2 O 3 , CEO 2 and TiO 2 The composition can be reduced by the increase in
[0023] (Soda-lime glass) SiO 2 :65~80% by mass Al 2 O 3 :0~5% by mass CaO: 5~15% by mass MgO: 2% by mass or more NaO: 10~18% by mass K 2 O: 0~5% by mass MgO+CaO: 5~15% by mass Na 2 O+K 2 O: 10~20% by mass SO 3 :0.05~0.3 mass% B 2 O 3 :0~5% by mass Fe 2 O 3 Total iron oxide (T-Fe 2 O 3 ):0.02~0.03% by mass
[0024] The thickness of the glass plate 1 is not particularly limited, but is preferably, for example, 2.4 to 4.6 mm, more preferably 2.6 to 3.4 mm, and particularly preferably 2.7 to 3.2 mm.
[0025] 2, the glass plate 1 is curved so as to be convex toward the exterior side of the vehicle, and a first functional film 2 is laminated on a concave surface 101 facing the interior side of the vehicle. The radius of curvature of the concave surface 101 may be, for example, 15,000 to 50,000 mm, and is preferably 30,000 to 50,000 mm. However, the glass plate 1 does not have to be curved and may be flat.
[0026] <1-2. First functional film> Next, a description will be given of the first functional film 2. The first functional film 2 according to this embodiment is formed of a water-repellent film having a water-repellent function.
[0027] This water-repellent film is characterized by containing an alkoxysilyl group, which is a coupling agent with the glass plate 1. The composition having a water-repellent function is not particularly limited, and may include, for example, a composition represented by the following formula (X). This composition contains only a composition that is substantially soluble in a fluorine-based solvent. "Only a composition that is substantially soluble in a fluorine-based solvent" does not mean, for example, that other compositions mixed in during the manufacturing process are excluded, but means that the mixing of other compositions of 1% by weight or less is permitted. However, the following is an example, and the water-repellent film may also be formed of other compositions.
[0028] [Rf 1― Z 1 ]a ― Q 1― [Z 2― SiR c M 3-c ] b (X) (In the formula, Rf 1 are independently a monovalent perfluoropolyether group having a molecular weight of 400 to 20,000 and composed of a perfluoroalkylene group having 1 to 6 carbon atoms and an oxygen atom, and Z 1 are each independently a divalent hydrocarbon group having 1 to 20 carbon atoms which may contain an oxygen atom, a nitrogen atom, or a silicon atom, and which may contain a cyclic structure in the middle. 2 are independently divalent hydrocarbon groups having 2 to 8 carbon atoms. 1 is a linking group having a valency of (a+b) containing at least (a+b) silicon atoms, and may form a cyclic structure. a is an integer of 1 to 10, b is independently an integer of 1 to 10, and c is independently 0, 1 or 2. a Z groups enclosed in [ ] in formula (X) 1 and b Z 2 are all Q 1 Or Q 2 bonded to the silicon atom in the structure; R is independently a monovalent hydrocarbon group having 1 to 6; M is an alkoxy group or an alkoxyalkyl group; ― SiR c M 3-c is an alkoxysilyl group. The fluorine-containing reactive silane compound represented by the following formula (1) can be exemplified as a composition that is substantially soluble in a fluorine-based solvent.
[0029] Examples of the fluorine-containing reactive silane compound represented by the above formula (X) include those shown below. [ka] [ka] [ka] [ka] [ka] (In the formula, r1 and Rf' are the same as above.)
[0030] The number average molecular weight of the fluoropolyether chain portion in the perfluoroalkylene group is not particularly limited, but is, for example, 1,000 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. 19 F ― The value is measured by NMR. If the number average molecular weight is 1,000 or more, the molecular bonds become longer, and for example, as shown in FIG. 3, even if oil adheres to the first functional film 2, the molecules are prevented from collapsing, and the deterioration of the water repellency can be prevented. On the other hand, if the number average molecular weight is too large, the number of alkoxysilyl groups bonded to the glass plate 1 may decrease. Therefore, if the number average molecular weight is 30,000 or less, the number of bonds with the OH groups of the glass plate 1 decreases, and the deterioration of the bond strength can be prevented.
[0031] Furthermore, when the number average molecular weight of the fluoropolyether chain portion is less than 1,000, that is, when the molecular weight is small, the first functional film is light, and even if it contains an alkoxysilyl group, the reaction probability on the surface of the glass plate 1 may decrease. As a result, the abrasion resistance may decrease. Therefore, when the molecular weight is less than 1,000, measures such as providing a base layer to improve the abrasion resistance are required.
[0032] The water-repellent function means, for example, that the contact angle on the surface of the first functional film is 60° or more, preferably 80° or more, and more preferably 100° or more.
[0033] The composition constituting the first functional film 2 is dissolved in a fluorine-based solvent and then laminated on the glass plate 1 by a method described below. Examples of the fluorine-based solvent include perfluorohexane, perfluorooctane, perfluoromethylcyclohexane, perfluorodimethylcyclohexane, perfluorodecalin, perfluoroalkylethanol, perfluorobenzene, perfluorotoluene, perfluoroalkylamine (Fluorinert (trade name) and the like), perfluoroalkylether, perfluorobutyltetrahydrofuran, polyfluoroaliphatic hydrocarbon (Asahiclean AC6000 (trade name)), hydrochlorofluorocarbon (Asahiclean AK ― 225 (trade name), etc.), hydrofluoroether (Novec (trade name), HFE ― 7100 (product name), HFE ― 7200 (product name), HFE ― 7300 (product name), HFE ― 7000 (product name), Asahiklin AE ― 3000 (product name) etc.), 1,1,2,2,3,3,4 ― Heptafluorocyclopentane, 1,1,1,3,3 ― Pentafluorobutane, fluorine-containing alcohol, perfluoroalkyl bromide, perfluoroalkyl iodide, perfluoropolyether (Krytox (trade name), Demnum (trade name), Fomblin (trade name), etc.), 1,3 ― Bistrifluoromethylbenzene, methacrylic acid 2 ― (Perfluoroalkyl)ethyl acrylate 2 ― (Perfluoroalkyl)ethyl, perfluoroalkylethylene, fluorocarbon 134a, and hexafluoropropene oligomers, 1,2 ― Dichloro ― 1,3,3,3 ― Tetrafluoroethylene ― 1 ― Propene and the like.
[0034] <2. Physical properties and performance of the first function> <2-1. Film thickness> The thickness of the first functional film 2 is not particularly limited, but is preferably 5 to 50 nm, and more preferably 10 to 30 nm. If the thickness of the first functional film 2 exceeds 50 nm, the cost may be high. On the other hand, the first functional film 2 exhibits a water-repellent function even with a thin thickness such as a monolayer, but if the thickness is less than 5 nm, for example, there is a risk that the film may peel off from the glass plate 1 when an external force is applied before drying. Therefore, the thickness of the first functional film 2 is preferably 5 nm or more. The thickness can be calculated by various methods, but for example, it can be measured by cutting the side glass at the place where the thickness is to be measured and observing the cross section with a SEM or the like.
[0035] Observation with the SEM can be performed, for example, as follows. A field emission scanning electron microscope S-4700 (manufactured by Hitachi High-Technologies Corporation) is used with an acceleration voltage of 5 kV. The first functional film 2 is then etched with 0.1% hydrogen fluoride. After that, a Pt-Pd coating is performed for conductive treatment, and observation with the SEM is performed.
[0036] Furthermore, if the film thickness is large, for example, the above-mentioned alkoxysilyl groups may become excessive, and those that are not bonded to the glass plate 1 may appear on the surface of the first functional film 2, forming irregularities. Such irregularities may hinder the smooth flow of water droplets, and as a result, the water repellency may be reduced.
[0037] <2-2. Surface roughness Ra> The surface roughness Ra of the first functional film 2 is preferably 0.5 to 3.0 nm, and more preferably 0.5 to 2 nm. This is because if the surface roughness Ra is less than 0.5 nm, the adhesion of the first functional film 2 to the glass plate 1 may decrease. On the other hand, if the surface roughness Ra exceeds 3.0 nm, adhering water droplets may become easily caught, and the water repellency may decrease. The surface roughness can be measured as follows. The surface shape was measured in cyclic contact mode using an atomic force microscope ("SPA400", Hitachi High-Tech Science Corporation), and the arithmetic mean roughness Ra was calculated. The cantilever used was a silicon "SI ― The measurement area of the sample was a 1 μm x 1 μm square, the number of measurement points was 512 x 256, the scan speed was 1.02 Hz, and correction was performed using a low-pass filter and leveling correction of the measurement data to calculate the surface roughness (Ra). The leveling correction of the measurement data was performed by fitting a curved surface using least squares approximation, correcting the data inclination, and removing distortion in the height direction.
[0038] <2-3. Water contact angle> It is particularly preferable that the contact angle of water on the first functional film 2 is 100° or more. The larger this contact angle, the better the static water repellency. It is also known that the contact angle is generally 120° or less. The contact angle is measured, for example, with 3 μL of water using a contact angle measuring device ("DMs-401", manufactured by Kyowa Interface Science Co., Ltd.).
[0039] <2-4. Water Fall Angle> The sliding angle is used as a measure of the ability of a water droplet to roll down the surface of the first functional film 2. The measurement method is described below. To measure the sliding angle, a water droplet with a diameter of 5 mm is placed on the surface (e.g., near the center) of the horizontally placed first functional film 2, and the glass plate 1 is gradually tilted. The tilt angle of the glass plate 1 at which the water droplet placed on the surface begins to roll is taken as the sliding angle of the water droplet. The sliding angle measured in this manner is preferably 20° or less, more preferably 15° or less, and particularly preferably 12° or less. The smaller the sliding angle, the better the dynamic water repellency, which indicates, for example, that raindrops that adhere to the surface are more likely to scatter while driving and thus do not obstruct the visibility of the occupants.
[0040] <2-5. Abrasion test> The abrasion test can be carried out, for example, as follows: A dry flannel cloth (No. 300) is attached to a reciprocating abrasion tester ("HEIDON-18" manufactured by Shinto Scientific Co., Ltd.), and a load of 1200 g / 4 cm is applied to the surface of the first functional film 2. 2 The first functional film 2 is then subjected to 1,500 reciprocating motions while applying a load of 100° to the first functional film 2. After this test, it is preferable that the contact angle of water on the first functional film 2 is 100° or more. If the contact angle of water on the first functional film 2 is 100° or more even after such an abrasion test, degradation of the water repellency can be suppressed even if friction occurs, for example, when another object comes into contact with the first functional film 2.
[0041] <3. Manufacturing method of side glass> Next, a method for manufacturing the side glass will be described. First, a curved glass plate 1 is formed by known press molding or the like. Then, this glass plate 1 is transported by a conveyor or the like with the concave surface 101 facing upward. During this transport process, a pretreatment is performed on the concave surface 101 of the glass plate 1 before the first functional film 2 is applied. The pretreatment is not particularly limited, but examples thereof include plasma treatment (corona discharge, etc.), ion beam treatment, alkali cleaning, and Cerico cleaning. Such treatment can introduce or increase hydroxyl groups on the surface of the concave surface 101 of the glass plate 1, and can also clean the concave surface 101 by removing foreign matter, etc.
[0042] It should be noted that after Cerico cleaning, the surface of glass plate 1 becomes hydrophilic, so the contact angle of the surface of glass plate 1, i.e., the surface before first functional film 2 is laminated, is 100° or more. In addition, the surface roughness of glass plate 1 is reduced after Cerico cleaning. In particular, because the thickness of first functional film 2 is thin, the surface roughness Ra of the first functional film follows the surface roughness of the surface of glass plate 1. As a result, the surface roughness Ra of the first functional film can be kept within the above-mentioned range, i.e., 3 nm or less.
[0043] Next, the coating liquid for the first functional film 2 is applied to the concave surface 101 by spraying. The method of application using a spray device is not particularly limited, but for example, the glass plate 1 is transported by a conveyer as shown in Fig. 5. At this time, the glass plate 1 is transported in a direction perpendicular to the paper surface of Fig. 5.
[0044] The spray device is provided with two nozzles 5 arranged in parallel above the glass plate 1. From each nozzle, the coating liquid for the first functional film 2 is sprayed toward the glass plate below at a coating angle θ of 100° or less. At this time, since the nozzles 5 are arranged close to each other, the coating liquid sprayed from the two nozzles 5 is applied so as to overlap. Since the coating liquid is sprayed from the nozzle 5 at a predetermined coating angle θ as described above, it is considered that the coating amount is the largest directly below the nozzle 5 on the concave surface of the glass plate 1, and the coating amount is small near the periphery. In addition, the coating amount is also large in the portion where the coating liquid sprayed from both nozzles 5 overlap. The height from the surface of the conveyor on which the glass plate 1 is placed to the nozzle 5 can be, for example, 20 to 80 mm. In addition, the discharge amount of the coating liquid from each nozzle 5 can be, for example, 50 to 200 g / min.
[0045] As described above, the coating liquid is discharged from the two nozzles 5 at a predetermined coating angle θ, and the coating liquid discharged from the two nozzles 5 is applied so as to overlap on the concave surface 101, so that unevenness is formed on the concave surface 101 along the surface direction. That is, as described above, the first functional film 2 after drying tends to be thickest near the center of the concave surface 101, but the film thickness also tends to be thick immediately below the nozzle 5, so the film thickness tends to be thin between them. Therefore, as shown in FIG. 6, at least three thick convex portions 21 and thin concave portions between them are formed in the direction perpendicular to the conveying direction of the glass plate 1. At this time, the distance L between the convex portions (the distance between the tops of the convex portions) is preferably, for example, 20 to 150 mm, and preferably 75 to 120 mm. This is because if the distance between the convex portions is less than 20 mm, the overall film thickness of the first functional film 2 becomes large, which may increase the cost. On the other hand, if the distance between the convex portions exceeds 150 mm, the film thickness of the first functional film 2 varies greatly, resulting in a non-uniform film thickness. For the sake of explanation, FIG. 6 exaggerates the unevenness of the film thickness.
[0046] In this embodiment, the coating liquid is sprayed from two nozzles 5, but three or more nozzles may be used. However, if the number of nozzles increases, it is considered that the number of projections and recesses formed in the first functional film 2 increases along the direction in which the nozzles are arranged, that is, along the surface direction perpendicular to the transport direction. Even in this case, it is preferable to set the distance L between the projections as described above.
[0047] After the coating liquid for the first functional film is applied to the concave surface 101 in this manner, moisture may be subsequently supplied to the surface of the coating liquid. By supplying moisture, hydrolysis may be expected in some cases.
[0048] Next, the glass plate may be heated, for example, at a temperature of 100 to 200° C. In such an atmosphere, groups bonded to Si in the composition constituting the first functional film rapidly undergo dehydration condensation, and as a result, promotion of bonding between the composition and the concave surface 101 may be expected.
[0049] Furthermore, since the fluorine-based solvent contained in the coating liquid evaporates quickly, the coating liquid flows toward the center along the concave surface 101 and hardens before pooling, thereby forming the first functional film 2.
[0050] <4. Features> The above-described side glass has the following advantages. (1) The first functional film 2 contains an alkoxysilyl group of a predetermined molecular weight as a coupling agent, which reacts with the OH group of the glass plate 1, improving the adhesion between the first functional film 2 and the glass plate 1. Therefore, the first functional film 2 can be directly laminated on the glass plate 1 without forming an underlayer. Furthermore, since the first functional film 2 has high adhesion, the contact angle of water on the first functional film 2 can be maintained at 100° or more even after the above-mentioned friction test. Furthermore, if an underlayer is not provided, the process of forming the underlayer is not necessary, thereby reducing costs.
[0051] However, when an undercoat layer is provided, the first functional film 2 peels off when rubbed, making the undercoat layer visible, resulting in a problem of poor scratch resistance. On the other hand, when an undercoat layer is not provided, scratch resistance is good, and a pencil hardness of generally 9H or more can be achieved. Note that the first functional film 2 also peels off when rubbed, but because the first functional film 2 is thin, this is difficult to see. Therefore, the window glass according to this embodiment is suitable for side glass that is frequently rubbed when going up and down.
[0052] In addition, direct lamination means that there is a covalent bond between the glass plate 1 and the first functional film 2, and further means that there are no components between the glass plate 1 and the first functional film 2 other than the composition of the glass plate 1 and the composition of the first functional film 2.
[0053] (2) The first functional film 2 contains only a composition soluble in a fluorine-based solvent. That is, the first functional film 2 is formed by applying a coating liquid containing an easily evaporating fluorine-based solvent and a composition soluble in the fluorine-based solvent to the glass plate 1. When such a coating liquid is applied to the concave surface 101 of the glass plate 1, the fluorine-based solvent evaporates before the coating liquid accumulates near the center of the concave surface 101, so that it is possible to suppress the occurrence of variations in the thickness of the first functional film 2 formed after the fluorine-based solvent has evaporated. Therefore, the amount of coating liquid applied to the concave surface 101 can be adjusted to a minimum, so that the amount of coating liquid used can be reduced. As a result, the manufacturing costs can be reduced.
[0054] (3) By making the film thickness of the first functional film 2 equal to or less than a predetermined value, it is believed that the unevenness of the surface of the first functional film 2 caused by excess alkoxysilyl groups is suppressed, and the thickness becomes uniform. Therefore, water droplets adhering to the first functional film 2 flow more easily, improving the water repellency. Furthermore, the improved water repellency can also suppress the adhesion of dirt, improving the antifouling performance.
[0055] <5. Modifications> Although one embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the spirit of the present invention. The following modified examples can be appropriately combined.
[0056] <5-1> In the above embodiment, the first functional film 2 is laminated only on the concave surface 101 of the glass plate 1, but a functional film can also be applied to the convex surface 102. Here, the functional film laminated on the convex surface 102 is referred to as the second functional film. For example, the first functional film 1 and the second functional film can contain the same composition having the water-repellent function as described above. In this case, the content of this composition can be the same. For example, in the state of the above-mentioned coating liquid, the content of the composition having the water-repellent function can be 0.1 to 0.5% by weight. On the other hand, after the solvent is evaporated, the content of the composition having the water-repellent function becomes 100% by weight. In this way, the first functional film 2 and the second functional film may be formed of the same material. Alternatively, the first functional film 2 and the second functional film may be formed of different materials. The first functional film 2 and the second functional film may have the same thickness or different thicknesses. In addition, the second functional film may be a film having a function other than the water-repellent function, for example, an AR function, a UV cut function, etc.
[0057] <5-2> The method for laminating the first functional film 2 is not particularly limited, and may be a method other than the above-mentioned spray method.
[0058] <5-3> The shape of the glass plate 1 is not particularly limited, and can be various shapes. In the above embodiment, the automotive window glass according to the present invention is applied to a side glass that can be raised and lowered, but the present invention is not limited to this, and can also be applied to fixed side glass, windshield, and rear glass that cannot be raised and lowered. The glass plate can be formed of a single plate or laminated glass. EXAMPLES
[0059] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0060] First, the glass plate and the first functional film used in the examples and comparative examples were prepared as follows.
[0061] (1) Glass plate A rectangular float glass plate having a size of 1000×500 mm and a thickness of 3 mm was prepared. This glass plate was curved, and the radius of curvature of the concave surface was 650 mm.
[0062] (2) First functional film As the first functional film to be applied to the concave surface of the glass plate, a first water repellent agent prepared by dissolving KY-1901 manufactured by Shin-Etsu Chemical Co., Ltd. in a fluorine-based solvent and a second water repellent agent prepared by dissolving SIT8175.0 manufactured by Gelest in alcohol were prepared and sprayed onto the glass plate, and then dried in the same manner as in the above embodiment. The first water repellent agent contains an alkoxysilyl group as a coupling agent and has an average molecular weight of 1,000 or more. On the other hand, the second water repellent agent has an average molecular weight of less than 1,000 as a coupling agent.
[0063] (3) Examples and Comparative Examples The first functional film was formed as follows: The glass plate was the same in the examples and the comparative examples, and the lamination method of the first functional film was as shown in the above embodiment. [Table 1]
[0064] (4) Evaluation The above-mentioned friction test was carried out on Examples 1 to 4 and Comparative Examples 1 and 2. The results are as follows. [Table 2]
[0065] (5) Discussion From the above test, in Examples 1 to 4, the water contact angle was 100° or more before and after the friction test. In addition, the water sliding angle was also kept at 15° or less before and after the test. On the other hand, in Comparative Examples 1 and 2, the water contact angle was 100° or less after the friction test. This is considered to be because the average molecular weight of the second water repellent agent is small (the average molecular weight of SIT8175.0 is 510) and even if it has an alkoxysilyl group, the reaction probability decreases, so the abrasion resistance is low. In addition, in Comparative Examples 1 and 2, the surface roughness before the test was 3.0 nm or more, which is larger than that of Examples 1 to 4, so it is considered that the water repellency is not high. This point is clear from the fact that the sliding angle before the friction test was 15° or more in all cases. [Explanation of symbols]
[0066] 1 Glass plate 101 Concave 2. First functional membrane
Claims
1. An automobile window glass comprising: A glass plate and a first functional film having a water-repellent function laminated on the glass plate without forming a base layer; Equipped with The first functional film contains a fluorine-containing reactive silane compound, The fluorine-containing reactive silane compound is a coupling agent having an alkoxysilyl group, the number average molecular weight of the fluoropolyether chain portion of the coupling agent having an alkoxysilyl group is 1,000 or more and 30,000 or less; A dry cloth of 1200 g / 4 cm is applied to the first functional film. 2 the contact angle of water on the first functional film is 100° or more after 1500 reciprocations under a load of The first functional film has a surface roughness Ra of 0.5 to 3.0 nm; the first functional film has a surface having projections and recesses formed thereon so that a thickness of the first functional film varies in a surface direction; The first functional film is formed so that the projections and recesses are aligned in one of the surface directions, and the pitch between adjacent projections is 20 to 150 mm.
2. 2. The automobile window glass according to claim 1, wherein the first functional film has a thickness of 5 to 50 nm.
3. 3. The automobile window glass according to claim 1, wherein a water sliding angle on the first functional film is 20° or less.
4. 4. The automotive window glass according to claim 1, which is a side glass that can be raised and lowered.
5. The first functional film is laminated on one surface of the glass plate, A second functional film is laminated on the other surface of the glass plate, 5. The automotive window glass according to claim 1, wherein the second functional film contains the same composition as a composition that exerts the water repellent function of the first functional film.
6. 6. The automotive window glass according to claim 5, wherein a content of the composition exhibiting the water-repellent function in the first functional film is the same as a content of the composition exhibiting the water-repellent function in the second functional film.
Citation Information
Patent Citations
Water-repellent composition, substrate having water-repellent layer, method for producing the same, and article for transportation equipment
JP2006206765A
Water repellent, oil repellent antifouling glass plate, its manufacturing method and automobile using the glass plate
JP2008137858A
Water repellent film-coated article, window glass for building, and window glass for vehicle
JP2010285574A